Institutional Explanations of Economic Development: the Role of Precious Metals - Elissaios Papyrakis; Reyer Gerlagh (Fondazione Eni Enrico Mattei (FEEM), 2005)
Recent research has emphasized the influence of colonization on the institutional development and economic performance in former European colonies. Where European colonizers settled, they replicated the investment-conducive institutions found at home. It has been argued that a harsh disease environment and a highly urbanized native population worked against colonization. We show evidence for another significant element explaining the endogenous character of colonization strategies and the formation of institutions. We find the presence of precious metals, gold and silver, to imply an increase in settlements, and an improvement in institutional quality, even when correcting for settlements. Highly valued gold and silver reserves attracted Europeans in large numbers and resulted in an institutional upgrade of mineral-rich areas.
Keywords: O13; O17; Q33; 330; Precious metals; Institutions; Economic development; Entwicklungstheorie; Institutionalismus; Edelmetall; Kolonialismus; Europa